Implementation of assessments in mathematics teacher learning during the covid-19 pandemic: A case study - Muhammad Bachtiar Aziz; Fajri Dwiyama (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2022)
The aims of this study were to: (1) provide an overview of the implementation of assessments in mathematics learning carried out by mathematics teachers at MAN 2 Bone during the covid-19 pandemic, (2) find out the obstacles and obstacles for MAN 2 Bone teachers in carrying out mathematics assessments during the pandemic. covid-19 The research method used is descriptive analysis with quantitative and qualitative approaches. Data were obtained through a questionnaire/questionnaire and interviews. The results showed that the implementation of the assessment carried out by MAN 2 Bone teachers in learning mathematics during the pandemic period was quite well implemented. Even so, there are still teachers who experience problems in carrying out math assessments during the COVID-19 pandemic, starting from the difficulty of assessing students' conceptual understanding of mathematics to the decision to determine the final grade of the semester during the COVID-19 pandemic.